PERENCANAAN STRUKTUR BETON BERTULANG PADA GEDUNG PASAR RAKYAT DI JALAN NIPAH KUNING DALAM: PERENCANAAN STRUKTUR BETON BERTULANG PADA GEDUNG PASAR RAKYAT DI JALAN NIPAH KUNING DALAM - Tobing, M.F.L; Abduh, M.; Hariyani, susi (Jurusan Teknik Sipil Polnep, 2023)
The third largest economic sector contribution is large and unit commerce, one example of which is the traditional market. Traditional markets that are visited by residents of Pontianak City are the traditional TPI Nipah Kuning market and the trifting jeruju market, but the two markets have their own problems. In an effort to improve the facilities and infrastructure that support buying and selling to be better, the author is planning a people's market building so that these problems can be resolved. The location of this traditional market building is on Nipah Kuning Dalam Street, Pontianak City. The planning of this traditional market building is based on the Medium Moment Bearing Frame System (SRPMM). This building is designed to be strenght against several loading combinations. The planning method of this building is assisted by the AutoCad program and the engineering analysis is assisted by the SAP 2000 3D program, as well as the calculation of building structures based on SNI 2847-2013, SNI 1727-2013, SNI 1726-2019, and using the Guidelines for Loading Planning for Houses and Buildings (PPPURG) 1987. The results of structural design in the form of thick slabs from 1st-4th floor and the flat roof have a slabs thickness of 120mm with Ø10-230 main reinforcement on floor slab, and Ø10-240 main reinforcement on flat roof, and Ø10-320 beugle reinforcement on floor slab and flat roof, the sloof beam dimensions of 80x65cm, secondary sloof beams dimensions of 60x30cm, primary beam dimensions of 80x40cm, secondary beam dimensions of 60x30cm, upper tie-beam dimensions of 80x40cm, secondary upper tie-beam dimensions of 60x30cm using D19 main reinforcement and Ø8 beugle reinforcement, dimensions of structural columns and pedestal columns 65x65cm with 24D19 main reinforcement, and Ø10 beugle reinforcement, foundation using piles 45x45 cm depth of 20 m with pile cap dimensions of 565x565cm and thick 92cm. Keywords: traditional market, solid concrete structures, earthquake-resistant buildings, spectrum response, structural calculations